Gallium Plasmonic Nanoantennas Unveiling Multiple Kinetics of Hydrogen Sensing, Storage, and Spillover. Issue 29 (2nd June 2021) - Losurdo, Maria; Gutiérrez, Yael; Suvorova, Alexandra; Giangregorio, Maria M.; Rubanov, Sergey; Brown, April S.; Moreno, Fernando
Abstract: Hydrogen is the key element to accomplish a carbon‐free based economy. Here, the first evidence of plasmonic gallium (Ga) nanoantennas is provided as nanoreactors supported on sapphire (α‐Al2 O3 ) acting as direct plasmon‐enhanced photocatalyst for hydrogen sensing, storage, and spillover. The role of plasmon‐catalyzed electron transfer between hydrogen and plasmonic Ga nanoparticle in the activation of those processes is highlighted, as opposed to conventional refractive index‐change‐based sensing. This study reveals that, while temperature selectively operates those various processes, longitudinal (LO‐LSPR) and transverse (TO‐LSPR) localized surface plasmon resonances of supported Ga nanoparticles open selectivity of localized reaction pathways at specific sites corresponding to the electromagnetic hot‐spots. Specifically, the TO‐LSPR couples light into the surface dissociative adsorption of hydrogen and formation of hydrides, whereas the LO‐LSPR activates heterogeneous reactions at the interface with the support, that is, hydrogen spillover into α‐Al2 O3 and reverse‐oxygen spillover from α‐Al2 O3. This Ga‐based plasmon‐catalytic platform expands the application of supported plasmon‐catalysis to hydrogen technologies, including reversible fast hydrogen sensing in a timescale of a few seconds with a limit of detection as low as 5 ppm and in a broad temperature range from room‐temperature up to 600 °C while remaining stable and reusable over an extended period of time. Abstract : Gallium nanoparticles represent a novel interesting plasmon photocatalysis system for hydrogen dissociation, sensing, and storage applications. Ga NPs have never been considered previously for photocatalysis. With respect to this, a novel vision is offered, which can represent breakthroughs in the plasmon‐activated photocatalysis as well as in hydrogen science and technology.